North-South Differences in the Impact of Forest Protection on Export Stability - Zhou, Hua; Wang, Jiacheng; Fan, Jiachen; Hao, Shiyu (Journal of Environmental Accounting and Management, 2026)
Forest conservation can generate far-reaching economic and trade effects, with significant heterogeneity across countries. This paper empirically examines the North-South disparities in the trade-related impacts of forest protection, focusing specifically on export stability. The findings reveal an inverted U-shaped relationship between forest cover in exporting countries and the stability of product exports from developed economies, while no significant effect is observed for developing countries. Mechanism analysis suggests that this impact in developed countries operates primarily through changes in domestic labor market characteristics and international labor mobility. Compared to high-tech products, the export stability of low-tech products is more susceptible to changes in forest coverage. Extended analysis indicates that promoting the adoption of industrial robots and the increases in health-related expenditures can help mitigate the potential adverse effects of increased forest cover. These findings contribute to a more comprehensive understanding and management of the potential trade-related effects of forest protection under varying national contexts.